Genetic variants in folate and cobalamin metabolism-related genes in nonsyndromic cleft lip and/or Palate - Waltrick-Zambuzzi, Márcia; Tannure, Patricia Nivoloni; Vieira, Thays Cristinedos Santos; Antunes, Leonardo Santos; Romano, Fábio Lourenço; Zambuzzi, Willian Fernando [UNESP]; Granjeiro, José Mauro; Küchler, Erika Calvano (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the association of the polymorphisms in TCN2 (rs1801198) gene and in MTRR (rs1801394) gene with nonsyndromic cleft lip and/or palate (NSCL/P) in a Brazilian population. Genomic DNA was extracted from buccal cells. The polymorphisms in TCN2 (rs1801198) and MTRR (rs1801394) genes were genotyped by carrying out real-time PCR and Taqman assay. Chi-square test was used to determine the association between genotype and allele frequencies with NSCL/P and NSCL/P subgroups (cleft lip only, cleft lip and palate, and cleft palate only). Eight hundred and sixty seven unrelated individuals (401 cases with NSCL/P and 466 individuals without cleft) were evaluated. Genotype distributions of TCN2 and MTRR polymorphisms were in Hardy-Weinberg equilibrium. The TCN2 polymorphic genotype GG was identified in 16.7% of the NSCL/P group and in 14.1% of the non-cleft group (p>0.05). Similarly, the frequency of MTRR genotype (GG) was similar in NSCL/P group (15.5%) and control group (17.8%) (p>0.05). Multivariate analysis showed an association between MTRR and the subgroup that the mother smoked during pregnancy (p=0.039). Our findings did not demonstrate an association between TCN2 polymorphisms and NSCL/P, however suggests an association between MTRR and NSCL/P etiology.
Keywords: Cleft lip and/or palate; Folic acid; Genetic polymorphisms; MTRR gene; Subphenotypes; TCN2 gene; Vitamin B12